Germany : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Recent Economic Developments and Selected Issues paper highlights that Germany's recovery from the 1993 recession, which had already been weaker than the previous three recoveries, stalled in the third quarter of 1995; output subsequently contracted in the fourth quarter of 1995 and first quarter of 1996. After rising by almost 3 percent in 1994 and at an annual rate of 2 1\2 percent (seasonally adjusted) during the first half of 1995, real GDP stagnated in the third quarter and fell by 0.6 percent (seasonally adjusted, annual rate) in the fourth quarter of 1995.